PERANCANGAN APLIKASI BANK SAMPAH BERBASIS ANDROID (STUDI KASUS : BANK SAMPAH HIMPUNAN MAHASISWA TEKNIK LINGKUNGAN UNIVERSITAS LAMBUNG MANGKURAT) - Fadlianoor Fadlianoor; Andy Mizwar; Muhammad Husin; Muhammad Abrar Firdaus (Prodi Teknik Lingkungan Fakultas Teknik Universitas Lambung Mangkurat, 2025)
The study aims to design an Android-based Waste Bank Application that is user-friendly and not eliminate the value of education regarding waste management. The study based on the problem of waste management within the campus which is still less regarded. Most of the waste in the campus environment will be directly disposed to a landfill. The implementation of conventional waste bank method has begun to be applied in several areas and campuses, yet there are obstacles in the activities of the conventional waste bank. The research method used in the study are written interviews and field observations, the application will be designed based on the data and processed from these methods. The application was made by colleagues from Information Technology, Lambung Mangkurat University, Banjarmasin which was designed by the author from the problem points obtained and according to the management of the Waste Bank HMTL FT ULM Banjarbaru. The results of the design of the Android-based waste bank